Traditional and Quantitative Assessment of Acid‐Base and Shock Variables in Horses with Atypical Myopathy. (29th November 2012) - van Galen, G.; Cerri, S.; Porter, S.; Saegerman, C.; Lefere, L.; Roscher, K.; Marr, C.; Amory, H.; Votion, D.M.
<x xml:space="preserve">Abstract</x> Background Descriptions of acid‐base disturbances in atypical myopathy (AM) are limited. Objectives Describe and compare traditional and quantitative acid‐base abnormalities and cardiovascular shock status in horses with AM at admission. Animals 34 horses with AM, 15 healthy controls. Methods Retrospective case‐control study. Records were searched for shock variables (packed cell volume [PCV], blood urea nitrogen [BUN], heart and respiratory rate) and acid‐base variables (venous blood gas analysis, electrolytes, total protein, lactate) on admission. Base excess (BE) of free water (BEfw), chloride (BEcl), total protein (BEtp), and unidentified anions (BEua), anion gap (AG), measured strong ion difference (SIDm), and concentration of total nonvolatile weak acids ([Atot]) were calculated. Acid‐base classifications, using simplified strong ion model and traditional approach, and shock grades were assigned. A 2‐sample Wilcoxon rank‐sum test and Bonferroni correction compared variables in AM cases versus control horses. Significance was P < .05/16 for acid‐base and P < .05/5 for shock variables. Results Tachycardia, tachypnea, and normal to increased PCV and BUN were common in AM cases. Respiratory, metabolic acid‐base alterations, or both were mainly caused by respiratory alkalosis, lactic acidosis, and SIDm alkalosis, alone or in combination. Evaluated variables (except pH, potassium concentration, total protein, and related calculations) were significantly different (P < .001) between AM cases and control horses. The strong ion model provided a more accurate assessment than the traditional approach and identified mixed derangements. Conclusions and clinical importance Acid‐base derangements should be evaluated in horses with AM and this preferably with the strong ion model.